Anisotropy and its Influence on a Metal Deposition Structure - Briland, Anders (My University, 2009)
Metal deposition is an additive manufacturing technique with many similarities to multilayer laser welding. Volvo Aero is interested in using the method in a future rocket exhaust nozzle structure. It is then important to understand what type of material characteristics the process produces and how this will influence the mechanical response of the structure. The present work consists of two parts: (i)a material investigation including optical microscopy, x-ray and electron backscatter diffraction of laser deposited Inconel 625 and (ii) a mechanical analysis of a rocket exhaust nozzle reinforcement including design of experiments to study the influence of anisotropy on elastic deformation and structural stability. The material investigations revealed dendritic solidified columnar grains orientated in the build direction, along with evidence that the material has a texture. The mechanical analysis indicate that the stiffness in tangential direction largely controls elastic deformation and that yield strength in the same direction controls margins to structural stability. For estimated levels of material properties, the influence of anisotropy created by metal deposition is expected to decrease the level of elastic deformation and structural stability margins with 1–5 %.
Keywords: Materialvetenskap; Konstruktionsmaterial; Materials Science; Construction materials